KECERDASAN EMOSIONAL DAN MOTIVASI KERJA DALAM MEMBENTUK KINERJA KARYAWAN: STUDI PENGALAMAN PADA MERAKI COFFEE & SPACE CIREBON - Annisa Fitriani; Melani Ayunurlita; Andini Febriany Mutiarasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to explore how emotional intelligence and work motivation contribute to employee performance at Meraki Coffee & Space Cirebon. This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews, observations, and documentation involving six employees selected using purposive sampling. The findings indicate that employees are able to manage their emotions effectively when facing work pressure and conflicts, while both intrinsic and extrinsic motivation play important roles in improving employee performance. Emotional intelligence and work motivation complement each other in fostering adaptability, communication, responsibility, and commitment at work. Therefore, emotional intelligence and work motivation are essential factors in enhancing employee performance in the service industry.